New option for anterior traction of the face by using a cervical collar - Neto, A. M. [UNESP]; Viterbo, F. [UNESP]; Palhares, A. [UNESP]; Bertoz, F. A. [UNESP]; Ferrari, L. E C [UNESP] (My University, 1995)
This case required anteroposterior traction of the maxilla. Once none of the traditional methods could be used because of the lack of support in the chin and in the frontal region. Thus, we opted to use a cervical collar.
Keywords: Cervical collar; Posterior traction; adult; case report; chin; clinical trial; face; human; male; maxilla; priority journal; traction therapy; Adult; Equipment Design; Human; Immobilization; Male; Maxilla; Maxillofacial Injuries; Neck; Traction